Integrasi Nilai-nilai Islam dalam Pembelajaran Matematika: (Studi Kasus Madrasah Aliyah Miftahul Ishlah, Lombok) - Apriliana, Feni; Fahrudin, Fadrik Adi; Pardi, M. Habib Husnial; Evendi*, Erpin (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study focuses on the Islamic values applied in Mathematics instruction and provides an in-depth examination of how these values are integrated into Mathematics learning activities at MA Miftahul Ishlah. The research employs a qualitative approach with a case study design, using observation, interviews, and documentation as data collection techniques. The findings of this study indicate that MA Miftahul Ishlah incorporates Islamic values into its mathematics instruction. These values include gratitude, ethics and morals, and social values. The value of gratitude is fostered through the routine practice of group prayers, which helps cultivate students' sense of thankfulness in the learning process, particularly in relation to their academic achievements and learning motivation. Activities based on tasks and discoveries conducted by the teacher help shape student behaviors such as honesty, fairness, exemplary conduct, and responsibility. These behaviors are aligned with ethical and moral values, which have a significant impact on student learning outcomes. Similarly, social values are cultivated through peer tutoring activities, categorized as non-formal learning activities. This activity fosters a sense of care and mutual assistance among students. Additionally, Quranic verses and Islamic terminology/examples/illustrations are employed in mathematics instruction, particularly when the material relates to numerical literacy.